Film and method for producing cured product using same

Through the use of inert oxidation to restore the induction system and magnetic auxiliary substrate in the membrane, the problem of high temperature or UV irradiation in the existing technology is solved, and the production of solvents without solvents at room temperature. It has excellent storage characteristics and uniformity CICF effect.

CN119384452APending Publication Date: 2025-01-28LG CHEM LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380047000.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-17
Filing Date
2023-06-16
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The prior art requires high temperature or UV irradiation when producing cured products, resulting in a reduction in the physical characteristics of the device, and contamination and quality problems caused by solvent volatility, and it is difficult for solvent-free compositions to achieve cured products with similar physical characteristics.

Method used

The membrane containing an inert oxidation reducing preparation system, through the design of the magnetic auxiliary substrate and the activation layer, can make the curing composition and the film leading agent component. reaction.

Benefits of technology

A solidification products produced without using high temperature or UV process have excellent storage characteristics and uniform solidification effects, and avoid the problem of decreased pollution and device physical characteristics caused by solvent volatilization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005186819110000211
    Figure BDA0005186819110000211
Patent Text Reader

Abstract

The present invention relates to a film and a method for producing a cured product using the same, and specifically relates to a film useful in an inert redox initiation system and a method for producing a cured product using the same. Specifically, the film according to the present invention comprises an auxiliary substrate having magnetism and an activation layer comprising an initiator component on a surface of the auxiliary substrate, in which a curing reaction is performed when a layer of a curable composition comprising a curable slurry, a filler component, and an initiator component is brought into contact with the initiator component of the film, and the initiator component is an inert redox initiation system comprising an oxidizing agent and a reducing agent, where the reducing agent may include a metal compound, and the metal compound may be included in an effective amount only in any one of the active layer of the membrane and the layer of the curable composition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to films and methods for producing cured products using the same, and in particular to films that can be used with inert redox initiator systems and methods for producing cured products. Background Art

[0002] As an existing method for producing a cured product, a solvent-based composition is mainly used, wherein the solvent-based composition substantially requires high temperature or UV irradiation during a curing process (eg, a volatilization process of a solvent).

[0003] However, if necessary, a curing process may be performed after applying the composition required to form a cured product to a specific device. In this case, the device to which the curable composition is applied is affected by high temperature or UV irradiation, thereby potentially causing a problem of deterioration in the physical properties of the device. When forming a cured product in this manner, there are cases where it is difficult to apply a high temperature or UV process.

[0004] Furthermore, solvent-based compositions lead to pollution problems during volatilization of the solvent and quality consequences due to gas generation.

[0005] To solve the above problems, a method of forming a cured product by minimizing the use of a solvent may also be considered, but achieving a cured product having physical properties similar to those of a solvent-based composition using a solventless composition is a difficult task. Summary of the Invention

[0006] Technical issues

[0007] Therefore, the problem to be solved by the present invention is to provide a cured product that can be produced without applying a separate high temperature or UV process using a film that can be used with an inert redox initiator system, and a method for producing a cured product using the same. The technical problems of the present invention are not limited to the technical problems described above, and those skilled in the art will clearly understand other technical problems that are not mentioned from the following description.

[0008] Technical Solution

[0009] The present invention can make many changes and can have many examples, thus specific examples will be shown in the drawings and described in detail. However, these are not intended to limit the present invention to specific embodiments, and should be understood to cover all changes, equivalents and alternatives included in the spirit and technical scope of the present invention.

[0010] In this specification, the term normal temperature or room temperature means a natural temperature without artificial heating or cooling, and may mean any temperature of about 10°C to 30°C, preferably 23°C to 27°C, depending on the season.

[0011] The terms used in this application are only used to describe specific examples and are not intended to limit the present invention. Unless the context clearly provides otherwise, singular expressions include plural expressions. In this application, it must be understood that terms such as "including" or "having" are intended to indicate the presence of features, quantities, steps, operations, components, parts, or combinations thereof described in the specification, but do not preclude the presence or addition of one or more additional features, or quantities, steps, operations, components, parts, or combinations thereof.

[0012] Unless otherwise defined, all terms used herein (including technical or scientific terms) have the same meaning as commonly understood by those skilled in the art to which the present invention belongs. Unless explicitly defined in this application, terms such as those defined in commonly used dictionaries should be interpreted as having a meaning consistent with the meaning in the context of the relevant technology, and should not be interpreted as an ideal or overly formal meaning.

[0013] In a specific embodiment according to the present invention, the present invention may relate to a film. More specifically, the film of the present invention relates to an inert redox system in combination with a layer of a curable composition, wherein the inert redox system is based on an inert redox initiator system. In this specification, "redox initiator system" means a system that initiates free radical polymerization at room temperature by a redox initiator, and specifically, means a system that initiates free radical polymerization by an electron transfer reaction based on free radicals generated by a redox reaction of the initiator. In particular, the present invention uses an inert redox initiator system, wherein in this specification, "inert redox initiator system" means a redox initiator system that is formulated so that redox is not possible with only a single initiator component.

[0014] In one example, the film according to the present application may include an auxiliary substrate having magnetism and an activation layer containing an initiator component on the surface of the substrate. Here, the auxiliary substrate is a magnetic layer containing magnetic particles, wherein the present application includes a magnetic layer, thereby enabling a process by magnetic force. Specifically, the film according to the present application can be fixed with sufficient magnetic force, and in addition, by further arranging a magnet on one side of the film to fully diffuse the initiator component in the activation layer and the layer of the curable composition, not only the side of the curable composition in contact with the activation layer is partially cured, but also the opposite side that is not in contact can be uniformly cured as a whole.

[0015] As long as the auxiliary substrate contains magnetic particles, its material is not particularly limited, but as an example, it may include one or more selected from iron, nickel, chromium, aluminum, zinc, silicon, and combinations of the foregoing.

[0016] In an example, described film can also comprise base material, if it comprises base material, then it can have the structure of base material, auxiliary base material and activation layer sequentially laminated.Different from auxiliary base material, base material can not comprise magnetic particles, and as long as the activation layer comprising initiator component can be arranged on the surface of auxiliary base material, base material can use without restriction, but an example can comprise polymer, plastics, metal, timber, leather or concrete etc.The example of polymer base material can comprise polymer based on cellulose acylate, cycloolefin polymer, based on polycarbonate polymer, based on acrylate polymer, based on polyester polymer, based on polyimide polymer etc., and is not limited to this.The example of plastic base material can comprise polyethylene terephthalate (PET), polyether sulfone (PES), polycarbonate (PC), polyarylate (Par), cycloolefin copolymer (COC) etc., and is not limited to this.Metal base material can comprise aluminium, copper, silver, iron, zinc, nickel, titanium and gold etc., and is not limited to this.

[0017] When a layer of a curable composition comprising a curable slurry, a filler component, and an initiator component is brought into contact with the initiator component of the activation layer in the film, the film can undergo a curing reaction. Therefore, the film according to the present invention can have excellent storage characteristics and provide a cured product that allows uniform overall curing when the curing reaction is carried out simply by bringing the film into contact with the layer of the curable composition, because the surface of the film in contact with the curable composition is not only partially cured, but also there is almost no difference in the degree of curing in the thickness direction of the film.

[0018] Meanwhile, in this specification, "curable syrup" means a unit that forms a polymer in the final cured product by curing or crosslinking, which may include an oligomer formed by polymerizing two or more monomers, or a polymer component and a monomer component. As an example, the curable syrup may include a monomer, a (partial) polymer, and a crosslinking agent, wherein if the monomer component is partially polymerized into a (partial) polymer according to the desired composition, some of the monomers are polymerized to form an oligomer or polymer, and the remaining monomers remain, thereby constituting the curable syrup component.

[0019] Therefore, in this specification, the term "monomer unit" such as a (meth)acrylate unit described below may refer to a monomer present in the curable syrup in a state of forming an oligomer or polymer, or a monomer that is not polymerized but contained in the curable syrup. Therefore, when calculating the content of the curable syrup in this specification, it means that the syrup components include not only components in a monomeric state that do not participate in polymerization, but also components that participate in polymerization.

[0020] In addition, as described below, the oxidizing agent and the reducing agent as initiator components are only used to initiate polymerization by generating free radicals, but are not introduced into the final cured product for the purpose of forming polymer units, thereby distinguishing it from the curable syrup, but some of the initiator components may also be present in the final cured product by being bound to the polymer.

[0021] In addition, in the present specification, the initiator component refers to a redox initiator, which may include an oxidant and a reducing agent. In the present specification, the oxidant and the reducing agent refer to components that participate in or assist in generating free radicals that initiate polymerization by participating in or assisting in an oxidation-reduction reaction under a redox initiator system.

[0022] The curable composition of the present invention comprises a curable syrup containing a monomer unit, a crosslinking agent and / or a (partial) polymer, a filler component and an initiator. The initiator is a concept covering a reducing agent and an oxidizing agent, which needs to be designed to have excellent solubility, compatibility, dispersion rate and reactivity between the components constituting the composition, without being limited thereto, but the following composition can be used in this application.

[0023] In one embodiment, the curable composition comprises a filler component. The term filler component means a component consisting of a filler, ie, a component comprising only a filler.

[0024] In one example, the filler component can include two or more types of fillers with different average particle sizes. In one example, the filler component can include three or more types of fillers with different average particle sizes, or can be composed of three to six types, three to five types, three to four types, or three types of fillers with different average particle sizes. That is, in one example, the filler component can also only include three to six types, three to five types, three to four types, or three types of fillers with different average particle sizes.

[0025] In another example, the filler component can show at least two peaks in the volume curve of the particle size distribution measured using laser diffraction. In one example, the filler component can show three or more peaks in the volume curve of the particle size distribution, or can show three to six peaks, three to five peaks, three to four peaks, or three peaks. For example, the range of filler components showing three peaks does not include filler components showing one, two, or four or more peaks.

[0026] The average particle size of the filler in the present application means the particle size at which the volume accumulation is 50% in the volume curve of the particle size distribution measured by the laser diffraction method, which may also be referred to as the median diameter. That is, in the present application, the particle size distribution is obtained on a volume basis by the laser diffraction method, and the particle size at the point where the cumulative value is 50% in the cumulative curve with the total volume set to 100% is set as the average particle size, wherein in another example, such an average particle size may be referred to as the median particle size or D 50 Particle size.

[0027] Therefore, here, two types of fillers having different average particle sizes may mean fillers having different particle sizes at a point where the cumulative value is 50% in a volume curve of the particle size distribution.

[0028] Generally, when two or more types of fillers having different average particle sizes are mixed to form a filler component, as many peaks as the types of the mixed fillers appear in the volume curve of the particle size distribution measured for the filler component using the laser diffraction method. Therefore, for example, when a filler component is formed by mixing three types of fillers having different average particle sizes, the volume curve of the particle size distribution measured for the filler component using the laser diffraction method shows three peaks.

[0029] The filler component may be a thermally conductive filler component. The term thermally conductive filler component means a filler component that functions to allow the curable composition to be cured to exhibit thermal conductivity to be described below.

[0030] As an example, the curable composition of the present application may contain a filler component in an amount of 200 parts by weight or more relative to 100 parts by weight of the curable slurry. In another example, the filler component may be contained in an amount of 250 parts by weight or more, 300 parts by weight or more, 350 parts by weight or more, 400 parts by weight or more, 450 parts by weight or more, 500 parts by weight or more, 550 parts by weight or more, 600 parts by weight or more, 650 parts by weight or more, 670 parts by weight or more, 700 parts by weight or more, or 730 parts by weight or more relative to 100 parts by weight of the curable slurry, and the upper limit thereof is not greatly limited, but may be 1,500 parts by weight or less, 1,400 parts by weight or less, 1,300 parts by weight or less, 1,200 parts by weight or less, 1,100 parts by weight or less, 1,000 parts by weight or less, 900 parts by weight or less, or 800 parts by weight or less.

[0031] That is, according to the present application, the curable composition can exhibit excellent thermal conductivity by containing a relatively excessive amount of a filler component and at the same time increasing the packing density by adjusting the particle size and / or ratio of the filler contained in the filler component, and can also provide a cured product that can be cured at room temperature by a redox initiator without any energy source such as separate UV or heat, and has desired physical properties.

[0032] The filler component included in the curable composition of the present application may satisfy the following General Formula 1.

[0033] [General formula 1]

[0034] 5≤D 50A / D 50C ≤100

[0035] In general formula 1, D 50A is the maximum average particle size of the filler component, and D 50C is the minimum average particle size of the filler component.

[0036] Here, when the filler component contains two or more types of fillers having average particle diameters different from each other, the maximum average particle diameter (D 50A ) may refer to the average particle size of the filler having the largest average particle size among the fillers contained in the filler component. Alternatively, in another example, the maximum average particle size (D 50A ) may mean a particle diameter of a peak appearing at a maximum particle diameter among peaks appearing in a volume curve of a particle size distribution measured for a filler component using a laser diffraction method.

[0037] Here, when the filler component contains two or more types of fillers having different average particle sizes from each other, the minimum average particle size (D 50C ) may refer to the average particle size of the filler having the smallest average particle size among the fillers contained in the filler component. Alternatively, in another example, the minimum average particle size (D 50C ) may mean a particle diameter of a peak appearing at the minimum particle diameter among peaks appearing in a volume curve of a particle size distribution measured for a filler component using a laser diffraction method.

[0038] In another example, D in the above general formula 1 can also be 50A / D 50CThe values ​​are further adjusted to within a range of 5 or greater, 7 or greater, 10 or greater, 13 or greater, 15 or greater, 17 or greater, 20 or greater, 23 or greater, 25 or greater, 27 or greater, 30 or greater, 32 or greater, 34 or greater, 36 or greater, 38 or greater, 40 or greater, or 42 or greater and / or within a range of 100 or less, 95 or less, 90 or less, 85 or less, 80 or less, 75 or less, 70 or less, 65 or less, 60 or less, 58 or less, 56 or less, 54 or less, 52 or less, 50 or less, 48 ​​or less, 46 or less, or about 44 or less.

[0039] As an example, the filler component of the curable composition in the present application can include a filler with at least three different average particle sizes. Such a filler component can show at least three peaks in the volume curve of the particle size distribution measured using a laser diffraction method. In order for the curable composition to be cured into a thermal conductivity showing a level higher than a certain level, it is generally necessary to apply an excessive filler, and according to the application, even when applied to the curable composition so as to include an excessive filler, the hardness and thermal conductivity of the desired composition can be effectively exerted. However, if the filler is included in excess, the viscosity of the curable composition comprising the filler may significantly increase, but due to the filler component application of the application, the filler with different average particle sizes that can satisfy the above general formula 1, even if excessive filler is applied to the curable composition, the viscosity of the curable composition etc. can also be maintained at an appropriate level.

[0040] In a specific example, the filler component may include a first filler having an average particle size greater than 40 μm and 200 μm or less, a second filler having an average particle size greater than 5 μm and 40 μm or less, and a third filler having an average particle size of 0.2 μm to 5 μm. The filler component may include three types of fillers, or may only include three types of fillers. In addition, when three types of fillers are included, the first filler may be a filler having the largest average particle size among the fillers included in the filler component, and the third filler may be a filler having the smallest average particle size among the fillers included in the filler component. Therefore, in this case, the average particle size of the first filler may be the maximum average particle size (D 50A ), and the average particle size of the third filler can be the minimum average particle size (D 50C ).

[0041] In another specific example, the volume curve of the particle size distribution measured using the laser diffraction method for the filler component can show that the particle size appears in a first peak greater than 40 μm and in a range of 200 μm or less, the particle size appears in a second peak greater than 5 μm and in a range of 40 μm or less, and the particle size appears in a third peak in a range of 0.2 μm to 5 μm. The volume curve of the particle size distribution can include at least three types of peaks, or can only show three types of peaks. In addition, when at least three types of peaks are included, the first peak can be a peak that appears at the maximum particle size in the peak represented by the volume curve, and the third peak can be a peak that appears at the minimum particle size in the peak represented by the volume curve. Therefore, in this case, the particle size at the first peak can be the maximum average particle size (D 50A ), and the particle size at which the third peak appears can be the minimum average particle size (D 50C ).

[0042] In another example, the average particle size of the first filler or the particle size at which the first peak appears can also be adjusted to be within the range of 190 μm or less, 180 μm or less, 170 μm or less, 160 μm or less, 150 μm or less, 140 μm or less, 130 μm or less, 120 μm or less, 115 μm or less, 110 μm or less, 105 μm or less, 100 μm or less, 95 μm or less, 90 μm or less, 85 μm or less, 80 μm or less, or about 75 μm or less and / or within the range of 61 μm or more, 62 μm or more, 63 μm or more, 64 μm or more, 65 μm or more, 66 μm or more, 67 μm or more, 68 μm or more, 69 μm or more, or 70 μm or more.

[0043] In addition, in another example, the average particle size of the second filler or the particle size at which the second peak appears can be adjusted to be greater than about 6 μm, greater than 7 μm, greater than 8 μm, greater than 9 μm, greater than 10 μm, greater than 11 μm, greater than 12 μm, greater than 13 μm, greater than about 14 μm, greater than 15 μm, greater than 16 μm, greater than 17 μm, greater than 18 μm, or greater than 19 μm and / or within the range of 39 μm or less, 38 μm or less, or 40 μm or less. m or less, 37 μm or less, 36 μm or less, 35 μm or less, 34 μm or less, 33 μm or less, 32 μm or less, 31 μm or less, 30 μm or less, 29 μm or less, 28 μm or less, about 27 μm or less, 26 μm or less, 25 μm or less, 24 μm or less, 23 μm or less, 22 μm or less, 21 μm or less, or 20 μm or less.

[0044] Furthermore, in another example, the average particle size of the third filler or the particle size at which the third peak appears can also be adjusted within the range of about 0.3 μm or greater, 0.4 μm or greater, or about 0.5 μm or greater and / or within the range of about 5 μm or less, 4.5 μm or less, about 4 μm or less, about 3.5 μm or less, about 3.3 μm or less, about 3 μm or less, about 2.4 μm or less, about 2.5 μm or less, about 2 μm or less, or about 1.7 μm or less.

[0045] When the filler component includes three types of fillers as above, the ratio (D1 / D2) of the average particle size of the first filler (D1) to the average particle size of the second filler (D2) may be in the range of about 3 to 20. In another example, the ratio (D1 / D2) may be 3.1 or more, 3.2 or more, 3.3 or more, 3.4 or more, or 3.5 or more, or may be about 19 or less, 18 or less, 17 or less, 16 or less, 15 or less, 14 or less, 13 or less, 12 or less, 11 or less, 10 or less, 9 or less, 8 or less, 7 or less, 6 or less, 5 or less, or 4 or less.

[0046] If the second filler and the third filler having sizes within the range are included together with the first filler, and their relationship satisfies the above General Formula 1, etc., high thermal conductivity can be effectively satisfied while maintaining the viscosity of the resin composition at an appropriate level.

[0047] In one example, the curable composition may include a filler component in an amount of 200 parts by weight or more relative to 100 parts by weight of the curable slurry. In another example, the filler component may be included in an amount of 250 parts by weight or more, 300 parts by weight or more, 350 parts by weight or more, 400 parts by weight or more, 450 parts by weight or more, 500 parts by weight or more, 550 parts by weight or more, 600 parts by weight or more, 650 parts by weight or more, or 700 parts by weight or more relative to 100 parts by weight of the curable slurry. The upper limit of the filler component is not significantly limited, but may be 2,000 parts by weight or less, 1,500 parts by weight, 1,000 parts by weight, or 900 parts by weight or less relative to 100 parts by weight of the curable slurry.

[0048] Meanwhile, when the first to third fillers are included in the filler component, about 10 to 90 parts by weight of the second filler and about 60 to 140 parts by weight of the third filler may be included relative to 100 parts by weight of the first filler. In another example, the ratio of the second filler relative to 100 parts by weight of the first filler may be about 15 parts by weight or more, about 20 parts by weight or more, about 25 parts by weight or more, about 30 parts by weight or more, about 35 parts by weight or more, about 40 parts by weight or more, about 45 parts by weight or more, or about 47 parts by weight or more, or may be about 85 parts by weight or less, about 80 parts by weight or less, about 75 parts by weight or less, about 70 parts by weight or less, about 65 parts by weight or less, about 60 parts by weight or less, about 55 parts by weight or less, or about 67 parts by weight or less. In another example, the ratio of the third filler can be about 65 parts by weight or more, about 70 parts by weight or more, about 75 parts by weight or more, about 80 parts by weight or more, about 85 parts by weight or more, about 90 parts by weight or more, or about 95 parts by weight or more, or can be about 135 parts by weight or less, about 130 parts by weight or less, about 125 parts by weight or less, about 120 parts by weight or less, about 115 parts by weight or less, about 110 parts by weight or less, or about 105 parts by weight or less.

[0049] As an example, the first filler may be present in an amount of about 10 parts by weight to about 60 parts by weight relative to 100 parts by weight of the total filler component, the second filler may be present in an amount of about 1 part by weight to about 40 parts by weight relative to 100 parts by weight of the total filler component, and the third filler may be present in an amount of about 10 parts by weight to about 60 parts by weight relative to 100 parts by weight of the total filler component.

[0050] In one example, the filler component can include a spherical filler in an amount of 30 wt % or more. Generally, if the shape of the filler is spherical, it is not conducive to achieving higher thermal conductivity. That is, with regard to thermal conductivity, it is advantageous to use a non-spherical filler. However, when the filler is non-spherical, it is disadvantageous with regard to the hardness of the cured product. Therefore, by including a spherical filler higher than a certain level in the filler component, a favorable effect can be exerted in terms of the hardness of the cured product. In addition, according to the composition of the present application, even at the content of the spherical filler as described above, high thermal conductivity can also be achieved. In another example, the content of the spherical filler in the filler component can be 35 wt % or greater, 40 wt % or greater, 45 wt % or greater, 50 wt % or greater, 55 wt % or greater, or 57 wt % or greater. Taking into account the thermal conductivity and hardness characteristics of the cured product material, the upper limit of the content of the spherical filler in the filler component can be adjusted within the range of 95 weight % or less, 90 weight % or less, 85 weight % or less, 80 weight % or less, 75 weight % or less, 70 weight % or less, or 65 weight % or less.

[0051] For example, if a non-spherical filler is present in the filler component, it is advantageous to select a filler having a small average particle size as the non-spherical filler. For example, if the filler component contains first to third fillers, a non-spherical filler may be selected as the third filler.

[0052] The term spherical filler is a filler having a sphericity of 0.9 or greater. In another example, the sphericity of the spherical filler can be 0.95 or greater. Therefore, a filler having a sphericity of less than 0.9 is a non-spherical filler.

[0053] Sphericity can be determined by particle shape analysis of the particles. In one specific example, the sphericity of a filler can be defined as the ratio (S' / S) of the surface area (S) of the particle to the surface area (S') of a sphere having the same volume as the particle. For actual particles, circularity is often used. Circularity can be expressed as the ratio of the boundary (P) of an image obtained from a two-dimensional image of an actual particle to the boundary of a circle having the same area (A) as the area of ​​the same image, and is obtained by the following equation.

[0054] <Circularity Equation>

[0055] Circularity = 4πA / P 2

[0056] Circularity is expressed as a value from 0 to 1, with a perfect circle having a value of 1 and more irregularly shaped particles having a value of less than 1.

[0057] As an example, filler component can be a thermally conductive filler component. As mentioned above, the term thermally conductive filler is a filler component that plays a role in making the curable composition be cured into a filler component that shows an effect of thermal conductivity of about 3.0W / mK or greater. Such filler component can include a filler made of a material with a thermal conductivity of about 1W / mK or greater, 5W / mK or greater, 10W / mK or greater, or about 15W / mK or greater. In another example, the thermal conductivity of the material can be about 400W / mK or less, 350W / mK or less, or about 300W / mK or less. The type of such material is not particularly limited, and it can be exemplified as, for example, ceramic material such as aluminum oxide (aluminum oxide: Al2O3), aluminum nitride (AlN), boron nitride (BN), silicon nitride (Si3N4), silicon carbide (SiC), beryllium oxide (BeO), zinc oxide (ZnO), magnesium oxide (MgO) or boehmite.

[0058] In addition to such thermally conductive fillers, the filler component may also contain various types of fillers if necessary, and for example, a carbon filler such as graphite, or a filler such as fumed silica, clay, aluminum hydroxide (Al(OH)3), magnesium hydroxide (Mg(OH)2) or calcium carbonate (CaCO3) may be applied.

[0059] In one example, the moisture content (water content) of the filler component can be about 1,000ppm or less. The moisture content can be measured with a Karl Fishcer titrator (KR831) under the conditions of 10% relative humidity and 5.0 or less drift. At this point, the moisture content can be the average moisture content of all filler components used in the resin composition. In the present application, filler components that meet the above conditions can also be selectively used, or the water content of the filler can also be adjusted to meet the above moisture content range by drying the filler component to be used in an oven at a temperature of about 200°C. In another example, the upper limit of the moisture content of the filler component can be about 800ppm or less, 600ppm or less, or about 400ppm or less, and its lower limit can be about 100ppm or more, or about 200ppm or more.

[0060] In addition, in a specific example of the present invention, the curable composition may include a reducing agent in a range of 0.05 to 10 parts by weight relative to 100 parts by weight of the curable slurry, which is not limited thereto, but as an example, the lower limit of the reducing agent content may be 0.1 parts by weight or more, 0.5 parts by weight or more, 1 part by weight or more, 1.5 parts by weight or more, 2 parts by weight or more, 2.5 parts by weight or more, 3 parts by weight or more, 3.5 parts by weight or more, 4 parts by weight or more, 4.5 parts by weight or more, 5 parts by weight or more, 5.5 parts by weight or more, or 62 parts by weight or more, and its upper limit may be 9.5 parts by weight or less, 9 parts by weight or less, 8.5 parts by weight or less, 8 parts by weight or less, 7.5 parts by weight or less, 7 parts by weight or less, 6.7 parts by weight or less, 6.5 parts by weight or less, or 6.3 parts by weight or less. By including the reducing agent in the above-mentioned content, the present invention can obtain a cured product that ensures sufficient curability to have desired physical properties.

[0061] In one example, the reducing agent may include a metal compound. According to the present invention, the metal compound is not significantly limited, as long as the layer of the curable composition and the layer of the initiator component are in direct contact with each other to initiate or promote the redox reaction without separate heat or UV irradiation, and the composition containing the reducing agent can be stably stored, and it is particularly preferred that it has excellent solubility, compatibility, dispersion rate and reactivity with the curable slurry.

[0062] The metal compound may be included in an effective amount only in the layer of the initiator component in the film and in any one of the layers of the curable composition. Here, an effective amount means an amount capable of initiating a significant oxidation-reduction reaction to produce a cured product. That is, the metal compound may be included in an effective amount only in the layer of the initiator component and in any one of the layers of the curable composition, and may not be substantially included in the other layer. As an example, when the metal compound is included in the layer of the initiator component in an effective amount, the metal compound may not be substantially included in the layer of the curable composition. In addition, as another example, when the metal compound is included in the layer of the curable composition in an effective amount, the metal compound may not be substantially included in the layer of the initiator component. Here, the meaning of being substantially not included can be the meaning of being included in 0% by weight, and even if the metal compound is included in the layer of the curable composition, it is included in 1% by weight or less, 0.5% by weight or less, or 0.1% by weight or less, so that it can be included in a trace amount rather than in an effective amount capable of initiating an oxidation-reduction reaction.

[0063] In addition, in the layer of the initiator component in the film and the layer of the curable composition, the layer containing the metal compound in an effective amount may substantially not contain an oxidant. That is, in the present invention, it is not possible to adopt a situation in which the oxidant and the metal compound are substantially contained in the same layer at the same time before forming the cured product. In other words, when the metal compound is contained in the layer of the initiator component in the film in an effective amount, the oxidant may not be contained in the layer of the initiator component in the film in an effective amount, but may be contained in the layer of the curable composition in an effective amount. As another example, when the metal compound is contained in the layer of the curable composition in an effective amount, the oxidant may not be contained in the layer of the curable composition in an effective amount, but may be contained in the layer of the initiator component of the film in an effective amount.

[0064] As an example, the metal included in the metal compound can be a transition metal, and the metal compound can be a salt or chelate or its hydrate comprising a metal ion, and can include one or more types. Here, the metal ion can be one or more selected from cobalt, iron, vanadium, copper, manganese, nickel, titanium, aluminum, tin, chromium, zinc, zirconium, indium, manganese and mixtures thereof. In detail, the metal compound can be a cobalt-containing component, wherein in the cobalt-containing component, cobalt can have an oxidation state of +2 valence or +3 valence. Available cobalt-containing components can include cobalt naphthenate, cobalt sulfide etc., but are not limited thereto. As another example, the metal compound can be an iron-containing component, wherein in the iron-containing component, iron can have an oxidation state of +2 valence or +3 valence. Available iron-containing components can include iron sulfate (III), ferrous sulfate (II), iron chloride (III), ferrous chloride (II), iron carboxylate, iron naphthenate, iron (III), iron (II) or ferric acetylacetonate (III), but are not limited thereto. As another example, the metal compound can be a vanadium-containing component, wherein in the vanadium-containing component, vanadium can have an oxidation state of +4 valence or +5 valence. Available vanadium-containing components can include vanadium acetylacetonate, vanadium oxystearate, vanadium naphthenate, vanadium benzoyl acetonate, vanadium oxalate, triisopropyl vanadium oxy (V), ammonium metavanadate (V), sodium metavanadate, vanadium pentoxide (V) or vanadium oxysulfate (V), but is not limited to this. As another example, the metal compound can be a copper-containing component, wherein in the copper-containing component, copper can have an oxidation state of +1 valence or +2 valence. Available copper-containing components can include a complex of copper acetate, copper chloride, copper benzoate, copper acetonate, copper naphthenate, copper carboxylate, copper salicylate, copper and thiourea or ethylenediaminetetraacetic acid, but is not limited to this. In addition, the metal compound can be exemplified as manganese naphthenate, nickel naphthenate, titanium acetylacetonate, copper sulfate, manganese sulfate or nickel sulfate etc.

[0065] Furthermore, the reducing agent may include an organic compound, wherein the organic compound is not significantly limited as long as it initiates or promotes an oxidation-reduction reaction by directly contacting a layer of the curable composition with a layer of the initiator component without separate heat or UV irradiation.

[0066] The organic compound may also be substantially contained together in the layer of the initiator component and the layer containing the oxidant in the layer of the curable composition in the film, and may also be substantially contained together in the layer containing the metal compound, but may be selectively and substantially contained only in the layer containing the oxidant or the layer containing the metal compound.

[0067] As an example, the organic compound may be at least one of the group consisting of amine, pyridine, aldehyde amine condensation compound, thiourea and derivatives thereof, and may also be two or more thereof. In detail, examples of the organic compound may include N, N-dimethyl-p-toluidine, N, N-dimethylformamide, triethylamine, N, N-diisopropyl-p-chloroaniline, N, N-diisopropyl-p-bromoaniline, N, N-diisopropyl-p-bromo-o-methylaniline, N, N-dimethyl-p-chloroaniline, N, N-dimethyl-p-bromoaniline, N, N-diethyl-p-chloroaniline, N, N-diethyl-p-bromoaniline, 3, 5-diethyl-1, 2-dihydro-1-phenyl-2-propylpyridine, N-benzoylthiourea or tetramethylthiourea, but are not limited thereto, and preferably, tertiary amine-based organic compounds may be used. In particular, the organic compound is preferably a compound that is in a liquid phase and has a half-life temperature in the range of 70°C to 170°C or in the range of 80°C to 150°C. By using an organic compound whose half-life temperature satisfies the above range, the present invention can suppress self-reaction in a storage state and can maintain the viscosity of the composition containing the organic compound at the desired level in the present invention. In this specification, the half-life is an indicator showing the decomposition rate of the compound, which means the time until the remaining amount of the compound is reduced to half.

[0068] In one example, when the reducing agent contains both a metal compound and an organic compound, the organic compound may be included in a range of 1 to 30 parts by weight relative to 100 parts by weight of the metal compound, and as an example, the lower limit thereof may be 2 parts by weight or more, 2.5 parts by weight or more, 3 parts by weight or more, 3.5 parts by weight or more, 4 parts by weight or more, 4.5 parts by weight or more, 5 parts by weight or more, 5.5 parts by weight or more, 6 parts by weight or more, 6.5 parts by weight or more, 7 parts by weight or more, 7.5 parts by weight or more, 8 parts by weight or more, 8.5 parts by weight or more, 9 parts by weight or more, 9.5 parts by weight or more, or 10 parts by weight or more, and the upper limit thereof may be 30 parts by weight or less, 27 parts by weight or less, 25 parts by weight or less, 23 parts by weight or less, 20 parts by weight or less, 17 parts by weight or less, 15 parts by weight or less, 13 parts by weight or less, or 12 parts by weight or less. The present invention can provide a cured product having excellent cured physical properties through a sufficient curing rate by containing the metal compound and the organic compound in the above weight ratio.

[0069] In addition, in one example, the curable composition may include an oxidant, wherein the oxidant is not significantly limited as long as it participates in an oxidation-reduction reaction to generate free radicals that initiate polymerization, and in particular, it is preferred that it has excellent compatibility with the curable slurry. As an example, the oxidant may include peroxides, peroxyesters, diacyl peroxides, or persulfates, but is not limited thereto, and specifically, as the oxidant, methyl ethyl ketone peroxide, tert-butyl hydroperoxide, p-menthane hydroperoxide, cumene hydroperoxide, diisopropylbenzene hydroperoxide, tert-butyl peroxylaurate, tert-butyl peroxybenzoate, tert-butyl peroxydecanoate, 1,5-di-tert-butylperoxy-3,3,5-trimethylcyclohexane, ethyl acetoacetate peroxide, benzoyl peroxide, hydrogen peroxide, or a combination thereof may be used.

[0070] In one example, the oxidizing agent may be included in a range of 5 to 70 parts by weight relative to 100 parts by weight of the reducing agent, and as an example, its lower limit may be 7 parts by weight or more, 10 parts by weight or more, 13 parts by weight or more, 15 parts by weight or more, 17 parts by weight or more, 20 parts by weight or more, 23 parts by weight or more, 25 parts by weight or more, or 30 parts by weight or more, and its upper limit may be 65 parts by weight or less, 60 parts by weight or less, 55 parts by weight or less, 53 parts by weight or less, 50 parts by weight or less, 47 parts by weight or less, 45 parts by weight or less, 43 parts by weight or less, 40 parts by weight or less, 37 parts by weight or less, or 35 parts by weight or less.

[0071] In a specific example, as described above, the curable paste can be a polymer component. In particular, the layer of the curable composition in the present application can include a curable paste together with a large amount of filler components. Therefore, as described below, by combining the curable paste with a specific component with a large amount of filler components, the present application can have excellent properties in terms of the compatibility between mixing characteristics and a large amount of filler components and the curable paste.

[0072] The curable composition may include the curable syrup in an amount of 3 wt % to 20 wt %, without being limited thereto, but as an example, the lower limit of the curable syrup may be 4 wt % or more, 5 wt % or more, 6 wt % or more, 7 wt % or more, 8 wt % or more, 9 wt % or more, or 10 wt % or more, and the upper limit thereof may be 19 wt % or less, 18 wt % or less, 17 wt % or less, 16 wt % or less, 15 wt % or less, 14 wt % or less, 13 wt % or less, or 12 wt % or less.

[0073] In one example, the curable syrup may include an alkyl (meth)acrylate unit, a monomer unit containing a polar functional group, and a crosslinking agent. As an example, the alkyl (meth)acrylate unit may be an alkyl (meth)acrylate having an alkyl group containing 4 to 20 carbon atoms, wherein the carbon number of the alkyl group may be, for example, 16 or less, 12 or less, or 8 or less. Such an alkyl (meth)acrylate may be included in the curable syrup in an amount of about 1% to 12% by weight. In another example, the upper limit of the ratio may be 1.5 weight % or more, 2 weight % or more, 2.5 weight % or more, 3 weight % or more, 3.5 weight % or more, 4 weight % or more, 4.5 weight % or more, 5.2 weight % or more, 5.5 weight % or more, or 5.7 weight % or more, and the lower limit thereof may be 11.5 weight % or less, 11 weight % or less, 10.5 weight % or less, 10 weight % or less, 9.5 weight % or less, 9 weight % or less, 8.5 weight % or less, 8 weight % or less, 7.5 weight % or less, 7 weight % or less, or 6.5 or less.

[0074] The alkyl group in the (meth)acrylate unit may be a linear or branched aliphatic alkyl group, and may be substituted or unsubstituted. As the linear or branched aliphatic alkyl (meth)acrylate, for example, any one or two or more selected from the group consisting of n-butyl (meth)acrylate, tert-butyl (meth)acrylate, sec-butyl (meth)acrylate, amyl (meth)acrylate, 2-ethylbutyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, lauryl (meth)acrylate, and tetradecyl (meth)acrylate may be used.

[0075] The curable syrup may include a polar functional group-containing monomer unit as an additional component. The curable syrup may include a hydroxyl group-containing monomer unit, a carboxyl group-containing monomer unit, or an epoxy group-containing monomer unit as the polar functional group-containing monomer unit, but is not limited thereto.

[0076] As the monomer having a polar functional group, for example, hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate and / or 8-hydroxyoctyl (meth)acrylate (wherein the carbon number of the alkyl group may be 1 to 20, 1 to 16, 1 to 12, 1 to 8 or 1 to 4, and the alkyl group may be linear or branched, or may be substituted or unsubstituted); or hydroxypolyalkylene glycol (meth)acrylates such as 2-hydroxypolyethylene glycol (meth)acrylate or 2-hydroxypolypropylene glycol (meth)acrylate; epoxy group-containing (meth)acrylates such as glycidyl (meth)acrylate; or acrylic acid; etc. may be used, without being limited thereto.

[0077] In one embodiment of the present application, the monomer unit having a polar functional group may be included in an amount of 500 parts by weight or more relative to 100 parts by weight of the (meth)acrylate unit, and in another example, the lower limit thereof may be 600 parts by weight or more, 700 parts by weight or more, 800 parts by weight or more, 900 parts by weight or more, 1,000 parts by weight or more, 1,100 parts by weight or more, 1,200 parts by weight or more, 1,300 parts by weight or more, or 1,400 parts by weight or more, and the upper limit thereof may be 3,000 parts by weight or less, 2,500 parts by weight or less, 2,000 parts by weight or less, 1,700 parts by weight or less, 1,650 parts by weight or less, 1,600 parts by weight or less, 1,550 parts by weight or less, or 1,500 parts by weight or less.

[0078] Furthermore, the curable syrup of the present invention may further contain monomer units other than the foregoing, if necessary.

[0079] For example, the curable syrup may further comprise nitrogen-containing reactive monomer units. Such nitrogen-containing reactive monomers may be exemplified by one or two or more of the following: (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-isopropyl(meth)acrylamide, N-methylol(meth)acrylamide, diacetone(meth)acrylamide, N-vinylacetamide, N,N'-methylenebis(meth)acrylamide, N,N-dimethylaminopropyl(meth)acrylamide, N,N-dimethylaminopropyl(meth)acrylamide, N-vinylpyrrolidone, N-vinylcaprolactam or (meth)acryloylmorpholine, but are not limited thereto. Suitable monomers may be exemplified by, for example, (meth)acrylamide, N-alkyl(meth)acrylamide and / or N,N-dialkyl(meth)acrylamide, etc. Here, the alkyl group can be exemplified by a linear, branched or cyclic substituted or unsubstituted alkyl group having 1 to 20 carbon atoms, 1 to 16 carbon atoms, 1 to 12 carbon atoms, 1 to 8 carbon atoms, or 1 to 4 carbon atoms.

[0080] If necessary, the curable composition according to one embodiment of the present application may further include a crosslinking agent. The crosslinking agent can form a cured product having appropriate adhesion and hardness by achieving a crosslinking structure with the components included in the curable syrup.

[0081] As a cross-linking agent, for example, an acrylate cross-linking agent based on carbamate, an aliphatic isocyanate cross-linking agent, an epoxy cross-linking agent, an aziridine cross-linking agent and a metal chelate cross-linking agent can be used, without being limited thereto. In addition, as a cross-linking agent, one or two or more types can be used. The acrylate cross-linking agent based on carbamate is a compound having a plurality of carbamate bonds (-NHCOO-) in its molecular chain and an acrylic acid group capable of reacting with ultraviolet rays at the molecular end, and commercial PU330 (Miwon Commercial), PU256 (Miwon Commercial), PU610 (Miwon Commercial) and PU340 (Miwon Commercial) can be used. The aliphatic isocyanate cross-linking agent is, for example, an isocyanate compound such as isophorone diisocyanate, methylene dicyclohexyl diisocyanate or cyclohexane diisocyanate, but derivatives thereof such as dimers or trimers can also be used. As epoxy crosslinking agents, for example, ethylene glycol diglycidyl ether, triglycidyl ether, trimethylolpropane triglycidyl ether, N,N,N',N'-tetraglycidylethylenediamine or glycerol diglycidyl ether can be used. As aziridine crosslinking agents, for example, N,N'-toluene-2,4-bis(1-aziridinecarboxamide), N,N'-diphenylmethane-4,4'-bis(1-aziridinecarboxamide), triethylenemelamine, bisisophthaloyl-1-(2-methylaziridine) or tris-1-aziridinylphosphine oxide can be used. As metal chelate crosslinking agents, for example, metal chelate components can be used, which are compounds in which a polyvalent metal (e.g., aluminum, iron, zinc, tin, titanium, antimony, magnesium and / or vanadium) is coordinated with acetylacetone or ethyl acetoacetate.

[0082] The method for preparing the curable syrup containing such units is not particularly limited. For example, in order to achieve the above-mentioned syrup composition, the curable syrup can be formed by mixing monomers at a desired ratio and then appropriately partially polymerizing the mixture.

[0083] According to the present invention, it is possible to produce a cured product with the physical properties desired by the present invention only by contacting the layer of the initiator component in the film of the layer comprising the initiator component on the surface as described above. That is, the application can provide a cured product with desired hardness and physical properties without the need for separate heat or UV irradiation, because the curing reaction starts at room temperature and proceeds at room temperature. However, it is also possible to add a heat or UV irradiation step as needed. Curing can be carried out by the redox polymerization reaction between the initiator component present on the surface of the initiator component of the curable composition and the film.

[0084] When layers having different components are brought into contact with each other and a metal compound diffuses into the contact layer, thereby initiating an oxidation-reduction reaction, a cured product of the present invention can be produced. However, if the curing reaction proceeds too quickly, the metal compound, etc., cannot sufficiently diffuse, and thus a cross-linking reaction between the curable slurries is difficult to occur, so that the cured product may not have uniform physical properties. Therefore, by having such a composition, the present invention can control the curing reaction rate of the curable composition according to the above production method to an appropriate level.

[0085] In the present invention, curable composition can be solvent-free composition.Here, solvent-free composition is the composition that is substantially free of solvent (aqueous solvent and organic solvent).Therefore, the content of aqueous solvent and organic solvent in curable composition can be 1 weight % or less, 0.5 weight % or less, 0.1 weight % or less, or can be substantially 0 weight %.That is, realize curable composition of the present invention to have such composition, make it can realize the physical property that is equal to or better than the physical property of solvent-based when being solvent-free, and can be applicable to inert redox system simultaneously.

[0086] In addition, the curable composition of the present invention may have a viscosity in the range of 10,000 cps to 30,000 cps, 15,000 cps to 25,000 cps, 17,000 cps to 23,000 cps, or 18,000 cps to 22,000 cps when measured at a temperature of 25° C. and a shear rate of 1 rpm. The viscosity may be measured at room temperature using a Brookfield HB viscometer using a No. 63 spindle.

[0087] The cured product according to the present application may have thermal conductivity, and specifically, the thermal conductivity of the cured product may be 0.1 W / mK or greater. It is not limited thereto, but as an example, the thermal conductivity of the cured product may also be about 50 W / mK or less, 45 W / mK or less, 40 W / mK or less, 35 W / mK or less, 30 W / mK or less, 25 W / mK or less, 20 W / mK or less, 15 W / mK or less, about 10 W / mK or less, 9 W / mK or less, 8 W / mK or less, 7 W / mK or less, 6 W / mK or less, 5 W / mK or less, or about 4 W / mK or less. The thermal conductivity of the cured product may be measured, for example, according to ASTM D5470 standard or ISO 22007-2 standard. The cured material according to the present application exhibits the above thermal conductivity, so that it may be useful in various applications, and in particular, it may effectively discharge heat generated inside the battery module to the outside.

[0088] In another specific embodiment of the present application, a method for producing a cured product may be provided. The method for producing a cured product may include the following steps: providing a film including a layer of an initiator component on a surface of an auxiliary substrate having magnetic properties; and contacting a layer of a curable composition including a curable slurry, a filler component, and an initiator component with the layer of the initiator component of the film including a layer of the initiator component on the surface.

[0089] The same applies to the respective compositions as described above. The initiator component is an inert redox initiator system comprising an oxidizing agent and a reducing agent, wherein the reducing agent may comprise a metal compound, and the metal compound may be contained in an effective amount only in either the initiator component layer or the curable composition layer on the film.

[0090] The method of bringing the layer of the curable composition into contact with the layer of the initiator component of the film including the layer of the initiator component on the surface is not particularly limited, but as an example, the curable composition may be applied directly to the film, or may be applied to an arbitrary substrate and then laminated. In addition, when the layer of the initiator component of the film including the layer of the initiator component on the surface is brought into contact with the layer of the curable composition, the layer of the initiator component of the film including the layer of the initiator component on the surface may be brought into contact with one or both sides of the layer of the curable composition.

[0091] Beneficial effects

[0092] According to an example of the present invention, by using a one-component curing method rather than a two-component curing method in which a main agent and a curing agent are separated and mixed and then applied, a film for producing a cured product having excellent storage characteristics and capable of curing even under reaction conditions of room temperature and darkness without separate UV or heat, and a method for producing a cured product using the film are provided. DETAILED DESCRIPTION

[0093] Hereinafter, preferred experimental examples are presented to help understand the present invention. However, the following experimental examples are only intended to help understand the present invention, and the present invention is not limited to the following experimental examples.

[0094] Preparation of free radical polymer (P)

[0095] 2-Ethylhexyl acrylate (2-EHA) and 2-hydroxyethyl acrylate (HEA) were added to a flask equipped with a mechanical stirrer at a weight ratio of 60:40 (2-EHA:HEA). A solution containing Irgacure 184 as a photoinitiator and ethyl acetate (EAC) diluted at a ratio of 1:1 was further added thereto in an amount of approximately 0.1% by weight relative to the total weight of the compounds added to the flask. Nitrogen gas was then introduced under normal pressure, the temperature was raised to approximately 60°C, and the mixture was irradiated with a metal halide lamp while stirring. Once the temperature reached 68°C, the nitrogen gas introduction and lamp irradiation were stopped, thereby obtaining a radical polymer (P) (solids content: approximately 12%).

[0096] At this time, the prepared free radical polymer (P) had a viscosity of about 11,110 cps measured by Brookfield's DV-3 using a No. 63 spindle at a temperature of 25° C. and a torque of 31.6%, a weight average molecular weight (Mw) of about 2,192,000 g / mol, and a polydispersity index (PDI) of about 3.08.

[0097] Preparation Example 1: Preparation of curable composition

[0098] The above-prepared free radical polymer (P), 2-hydroxyethyl acrylate (2-HEA) and glycidyl methacrylate (GMA) were used as the curable syrup, and multifunctional aliphatic urethane acrylate (SUO-1020 of SHIN-AT&C) was used as the crosslinking agent (H), and a phosphorus-based flame retardant (FR-119L of Chempia) was used as the flame retardant (N), a modified polyester dispersant (Disperbyk-111 of BYK) was used as the dispersant (D), a filler component (F), methyl ethyl ketone was used as the oxidizing agent (O), and the like was used as the crosslinking agent (H). The present invention relates to a curable composition comprising: an organic compound (A) comprising: an oxide (MEKP) and N,N-dimethyl-p-toluidine (DMPT), and these materials were added to a paste mixer at a weight ratio of approximately 1.17:7.48:2.49:0.59:1.76:0.1:86.05:0.23:0.07 (P:2-HEA:GMA:H:N:D:F:O:A) and fully stirred to prepare a curable composition having a viscosity of approximately 200,000 cps as measured using a Brookfield DV-3 at room temperature of 25° C. and a shear rate of 1 rpm.

[0099] As the filler component (F), spherical alumina having an average particle size of about 70 μm (BAK-70 of Bestrytech, sphericity of 0.95 or more), aluminum hydroxide having an average particle size of about 20 μm (DH-50P of Korea Alumina, sphericity of 0.95 or more), and rectangular alumina having an average particle size of about 1.6 μm (KLS-51 of Korea Alumina, sphericity of less than 0.9) were mixed and used in a weight ratio of about 34.42:17.21:34.42.

[0100] Preparation Example 2: Preparation of curable composition

[0101] The above-prepared free radical polymer (P), 2-hydroxyethyl acrylate (2-HEA) and glycidyl methacrylate (GMA) were used as the curable syrup, and a multifunctional aliphatic urethane acrylate (SUO-1020 of SHIN-AT&C) was used as the crosslinking agent (H), and a phosphorus-based flame retardant (FR-119L of Chempia) was used as the flame retardant (N), a modified polyester dispersant (D of BYK) was used as the dispersant (D), and a polyfunctional aliphatic urethane acrylate (SUO-1020 of SHIN-AT&C) was used as the crosslinking agent (H). isperbyk-111), a filler component (F), methyl ethyl ketone peroxide (MEKP) as an oxidant (O), and N,N-dimethyl-p-toluidine (DMPT) as an organic compound (A), which are added to a pulper at a weight ratio of about 0.5:3.7:1.2:0.48:1.71:0.1:92.05:0.2:0.06 (P:2-HEA:GMA:H:N:D:F:O:A) and stirred thoroughly.

[0102] As the filler component (F), spherical alumina having an average particle size of about 70 μm (BAK-70 of Bestrytech, sphericity of 0.95 or more), aluminum hydroxide having an average particle size of about 20 μm (DH-50P of Korea Alumina, sphericity of 0.95 or more), and rectangular alumina having an average particle size of about 1.6 μm (KLS-51 of Korea Alumina, sphericity of less than 0.9) were mixed and used in a weight ratio of about 36.82:18.41:36.82.

[0103] Example 1

[0104] A metal compound solution was prepared by diluting iron (III) acetylacetonate as the metal compound (M) in toluene to 15% by weight.

[0105] Then, after applying the metal compound solution on the iron mesh so that the weight ratio of the oxidizing agent, the organic compound, and the metal compound in the curable composition according to Preparation Example 1 was about 0.23:0.07:0.64 (O:A:M), it was dried at about 25° C. for 5 minutes and then dried on a hot plate at 100° C. for 5 minutes. Then, the iron mesh coated with the metal compound was placed on aluminum foil.

[0106] The curable composition prepared above was applied to contact the iron mesh provided on the aluminum foil and applied to the surface having the metal compound. At this time, the curable composition was applied to a thickness of 2T. Thereafter, a PET film was placed on the surface of the curable composition that was not in contact with the aluminum foil.

[0107] Example 2

[0108] A magnet was further provided on the PET film to move the iron mesh in the direction of the magnet.

[0109] Comparative Example 1

[0110] A metal compound solution was prepared by diluting iron (III) acetylacetonate as the metal compound (M) in toluene to 15 wt %. The metal compound solution was mixed with the curable composition prepared above and stirred thoroughly to obtain a weight ratio of the oxidant, the organic compound, and the metal compound of about 0.23:0.07:0.64 (O:A:M).

[0111] The mixture was applied to an aluminum foil to a thickness of 2T, and a PET film was placed on top.

[0112] Comparative Example 2

[0113] This was prepared in the same manner as in Example 1, except that the curable composition according to Preparation Example 2 was used.

[0114] In this case, the compatibility between the curable slurry and the filler component is reduced, thereby causing a cracking phenomenon and making it impossible to formulate.

[0115] Experimental Example 1: Hardness

[0116] The PET film attached to each of the cured products produced by Examples and Comparative Examples was removed, and the hardness of the side from which the PET film was removed was measured using a Shore A durometer at a temperature of about 25° C. The hardness value represents the average value after 3-point measurement.

[0117] Experimental Example 2: Total Mass Loss (TML)

[0118] The total mass loss was evaluated in the following manner. A sample having a thickness of about 2T was prepared by removing the PET film attached to each of the cured products produced by the Examples and Comparative Examples and cutting it into an aluminum disk suitable for a diameter of about 5 cm, and measuring the weight (A, unit: g) of the sample. Thereafter, immediately after the sample was placed at 150°C for 45 minutes, the weight (B, unit: g) of the sample was measured, and TML was calculated according to the following general formula 2. In the following, C is the weight (unit: g) of the aluminum attached to the cured product.

[0119] [General formula 2]

[0120] Total mass loss (TML, unit: %) = (AB) / (AC)×100

[0121] Table 1 below summarizes the results according to the above experimental examples.

[0122] In particular, in Table 1, the required time indicates the time required to reach the relevant hardness.

[0123] [Table 1]

[0124]

[0125] While the above embodiments have been described herein, those skilled in the relevant art will appreciate that various modifications and variations may be made therein without departing from the spirit and scope of the invention as described in the appended claims.

Claims

1. A film comprising an auxiliary substrate having magnetic properties and an activation layer containing an initiator component on the surface of the auxiliary substrate, wherein When a layer of a curable composition comprising a curable syrup, a filler component and an initiator component is brought into contact with the initiator component of the film, a curing reaction is performed, and The initiator component is an inert redox initiator system comprising an oxidizing agent and a reducing agent, wherein the reducing agent comprises a metal compound, and the metal compound is contained in an effective amount only in any one of the activating layer and the layer of the curable composition of the film.

2. The film according to claim 1, wherein The film further comprises a substrate, wherein the substrate comprises a polymer, plastic, metal, wood, leather, or concrete.

3. The film according to claim 1, wherein The curable composition includes the filler component in an amount of 200 parts by weight or more relative to 100 parts by weight of the curable syrup.

4. The film according to claim 1, wherein The filler component includes two or more types of fillers having average particle sizes different from each other, and the cured product satisfies the following General Formula 1: [General formula 1] 5≤D 50A / D 50C ≤100 in, D 50A is the maximum average particle size of the filler in the filler component, and D 50C It is the minimum average particle size of the filler in the filler component.

5. The film according to claim 1, wherein The filler component contains three types of fillers having average particle sizes different from each other.

6. The film according to claim 1, wherein The filler component includes: a first filler having an average particle size ranging from 60 μm to 200 μm or less; a second filler having an average particle size greater than 5 μm and 40 μm or less; and a third filler having an average particle size ranging from 0.2 μm to 5 μm.

7. The film according to claim 1, wherein The filler component includes fumed silica, clay, calcium carbonate (CaCO3), aluminum oxide (Al2O3), aluminum nitride (AlN), boron nitride (BN), silicon nitride (Si3N4), silicon carbide (SiC), beryllium oxide (BeO), zinc oxide (ZnO), aluminum hydroxide (Al(OH)3), boehmite, magnesium oxide (MgO), magnesium hydroxide (Mg(OH)2), or carbon filler as filler.

8. The film according to claim 1, wherein The curable composition includes the reducing agent in a range of 0.05 parts by weight to 10 parts by weight relative to 100 parts by weight of the curable syrup.

9. The film according to claim 1, wherein The metal compound is a salt or chelate containing a metal ion, or a hydrate thereof, and the metal ion is selected from cobalt, iron, vanadium, copper, manganese, nickel, titanium, aluminum, tin, chromium, zinc, zirconium, indium, manganese and a mixture thereof.

10. The film of claim 1, wherein The reducing agent further comprises at least one organic compound selected from the group consisting of amines, pyridine, aldehyde-amine condensation compounds, thiourea and derivatives thereof.

11. The film according to claim 10, wherein The organic compound is included in an amount ranging from 1 part by weight to 30 parts by weight relative to 100 parts by weight of the metal compound.

12. The film of claim 1, wherein The oxidizing agent includes peroxides, peroxyesters, diacyl peroxides or persulfates.

13. The film of claim 1, wherein The oxidizing agent is included in an amount ranging from 5 parts by weight to 70 parts by weight relative to 100 parts by weight of the reducing agent.

14. The film of claim 1, wherein The curable composition includes the curable syrup in an amount of 3 wt % to 20 wt %.

15. The film of claim 1, wherein The curable syrup comprises an alkyl (meth)acrylate unit, a monomer unit containing a polar functional group, and a cross-linking agent.

16. The film according to claim 15, wherein The polar functional group includes a hydroxyl group, an epoxy group, an isocyanate group, a glycidyl group, an alkenyloxycarbonyl group, a (meth)acryloyl group or an alkenyloxyalkyl group.

17. The film of claim 15, wherein The curable syrup includes the alkyl (meth)acrylate unit in an amount of 1 wt % to 12 wt %.

18. The film of claim 15, wherein The curable syrup includes the polar functional group-containing monomer unit in an amount of 500 parts by weight or more relative to 100 parts by weight of the alkyl (meth)acrylate unit.

19. The film of claim 15, wherein The curable syrup includes a hydroxyl group-containing monomer unit and an epoxy group-containing monomer unit as the polar functional group-containing monomer unit.

20. The film of claim 15, wherein The cross-linking agent includes a multifunctional acrylate compound, a multifunctional isocyanate compound or a urethane acrylate compound.

21. The film of claim 1, wherein The curing reaction is carried out at room temperature.

22. The film of claim 21, wherein The curing reaction proceeds through a redox polymerization reaction of the initiator component of the curable composition with the initiator component present in the activation layer of the film.

23. The film of claim 1, wherein The curable composition is solvent-free.

24. The film of claim 1, wherein The curable composition has a viscosity ranging from 10,000 cps to 30,000 cps measured at a temperature of 25° C. and a shear rate of 1 rpm.

25. The film of claim 1, wherein The cured product obtained according to the curing reaction has thermal conductivity.

26. A method for producing a cured product, comprising the steps of: providing the film according to claim 1 having a layer including an initiator component on a surface of an auxiliary substrate having magnetic properties; as well as A layer of a curable composition comprising a curable syrup, a filler component and an initiator component is brought into contact with the layer of the initiator component of the film including a layer of the initiator component on a surface thereof, wherein The initiator component is an inert redox initiator system comprising an oxidizing agent and a reducing agent, wherein the reducing agent comprises a metal compound, and the metal compound is contained in an effective amount only in any one of the layer of the initiator component and the layer of the curable composition on the film.

27. The method for producing a cured product according to claim 26, comprising: A step of bringing the layer of the initiator component of the film including the layer of the initiator component on the surface into contact with both sides of the layer of the curable composition.